Consistency of UML class, object and statechart diagrams using ontology reasoners. (February 2015) - Khan, Ali Hanzala; Porres, Ivan
Abstract: We propose an automatic approach to analyze the consistency and satisfiability of Unified Modeling Language UML models containing multiple class, object and statechart diagrams using logic reasoners for the Web Ontology Language OWL 2. We describe how to translate UML models in OWL 2 and we present a tool chain implementing this translation that can be used with any standard compliant UML modeling tool. The proposed approach is limited in scope, but is fully automatic and does not require any expertise about OWL 2 and its reasoners from the designer. Abstract : Highlights: Reasoning of UML models containing multiple class, object and statechart diagrams. Reasoning of UML models using logic reasoners for the Web Ontology Language OWL 2. We describe how to translate UML class, object and statechart diagrams in OWL 2. We present an automatic tool chain implementing UML to OWL 2 translations. The implemented tool can be used with any standard compliant UML modeling tool.